(untitled) (Journal of Computational Mathematics, 2021)
Numerical solutions of Riemann problems for 2-D scalar conservation law are given by a second order accurate MmB (local Meximum-minimum Bounds preserving) scheme which is non-splitting. The numerical computations show that the scheme has high resolution and non-oscillatory properties. The results are completely in accordance with the theoretical solutions and all cases are distinguished efficiently.